Perbedaan Keyakinan Guru Matematika SMP Ditinjau Dari Pengalaman Mengajar - Muhtarom, Muhtarom; Aprilia, Adinda Rachma (Jurnal Riset dan Inovasi Pembelajaran, 2024)
The experience a teacher has may influence his or her beliefs about mathematics. This research describes the beliefs of junior high school mathematics teachers from teaching experience. The respondents to this research were six teachers who had different teaching experiences. Interview techniques were used to obtain research data. To ensure the credibility of the research data, source triangulation was carried out. The results show that mathematics teachers with more than 30 years of teaching experience believe that mathematics is an absolute science, there are arguments for solving problems. Mathematics teachers with 11 – 30 years of teaching experience believe that mathematics covers various fields of science and various scientific disciplines require mathematics. This shows that all areas of life use mathematics. Mathematics teachers with less than 10 years of teaching experience believe that mathematics is a comprehensive science that is interconnected and integrated with social, historical, political and cultural practices. This research illustrates that teaching experience has an impact on differences in teachers' beliefs about mathematics.